Adverse effects of RBC transfusions in neonates: a systematic review and meta-analysis - Keir, A; Pal, S; Trivella, M; Lieberman, L; Callum, J; Shehata, N; Stanworth, S (Wiley, 2016)
Background Controversy exists regarding the contribution of blood transfusions to a range of adverse clinical outcomes in neonates. The aim of our systematic review was to identify the broader literature on harmful effects and associations potentially attributable to red blood cell (RBC) transfusions. Study Design A comprehensive search of MEDLINE (PubMed) and EMBASE was undertaken. Eligible studies included both randomized (RCT) and nonrandomized studies examining the effects of small volume (10-20mL/kg) RBC transfusions on neonates. Primary outcomes of interest were mortality, chronic lung disease, retinopathy of prematurity, necrotizing enterocolitis and intraventricular hemorrhage. Two independent authors conducted abstract, then full-text article reviews, as well as data extraction and quality assessments. Results Sixty-one studies were eligible for inclusion, including 16 (26%) randomized. The majority of studies were non-randomized studies (45; 74%), which included 32 observational studies with and 13 studies without a comparator group. There was no evidence that rates of mortality differed between restrictive and liberal strategies for transfusion (8 RCTs - RR: 1.24, 95% CI: 0.89-1.672, I^2 = 0%) or for NEC (5 RCTs - RR: 1.45, 95% CI: 0.91-2.33, I^2 = 0%). A liberal strategy was also not superior to restrictive transfusion practice in thepooled randomized studies for rates of ROP, CLD, or IVH. Conclusions Statistically significant differences in a range of harmful outcomes between neonates exposed to restrictive and libera lRBC transfusion practice were not found. However, the risks of bias identified in many studies and lack of consistent reporting and definitions of events limits our conclusions.